Makerspace Sound and Music Projects for All Ages - Glendening, Mary L.; Glendening, Isaac W. (New York; Chicago; San Francisco; Athens; London; Madrid; Mexico City; Milan; New Delhi; Singapore; Sydney; Toronto : McGraw-Hill Education, 2018)
The book features dozens of DIY projects complete with parts lists, start-to-finish instructions, and full-color illustrations that guarantee success. You will explore the latest inexpensive -- or free! -- audio software for Windows, Apple, iOS, and Android devices. Work with free and low-cost music apps and programs-Build unique musical instruments from household items-Choose a microphone that fits your needs and budget-Learn about DAWs and audio recording and editing applications-Start making sound with littleBits, Scratch, and MakeyMakey-Create killer drum beats and melodic sequences using micro: Bit-Record your music and use cutting-edge analog and digital effects-Add sound to your robotics, e-textile, 3-D printing, and wearable gadgets-Upload your audio creations to SoundCloud,YouTube, and iTunes.
Includes bibliographical references and index.
Keywords: Makerspaces; Audio-visual materials; Sound -- Study and teaching -- Activity programs